Bio-adsorption of Cationic-Cnionic Dyes from Synthetic Effluents using an Experimental Design Approach - Sami D. Salman; Zyad R. Zair; Ziad T. Alismaeel (Desalination and Water Treatment)
In the current research, Cycas leaves powder (CL) as a low-cost agro-waste adsorbent was investigated for malachite green (MG) and Indigo Carmine (IC) dye removal from contaminated water. The Cycas leaves powder was characterized by Scanning electron microscopy (SEM) with energy dispersive X-ray spectroscopy (EDX) and Fourier transform infrared (FTIR) techniques. The adsorption parameters were investigated including contact time, dye concentrations, and adsorbent dosage to determine their effects on the adsorption efficiency. The I-optimal design approach was used to intimately detect the significance of adsorption parameters and their interactions by analyzing the overall statistical results. The adsorption isotherm and kinetics were analyzed using two models. The results showed that the data was well-fitted with the Freundlich isotherm model and the adsorption kinetics followed the pseudo-first-order model. The thermodynamics parameters including ΔHº, ΔSº, and ΔGº were determined, and the adsorption process was non-spontaneous, and exothermic for MG and endothermic IC dyes. The results demonstrated that Cycas leave can be exploited as an affordable inexpensive material for the treatment of industrial dyes from textile discharges.